Affective phenotypes in heterozygous LRRK2 R1441G knock-in mice - Ng, Marcus H. F.; Lam, Jimmy W. Y.; Choi, Zoe Y. K.; Liu, Hui-Fang; Ho, Philip W. L.; Lau, Benson W. M.; Yee, Benjamin K. (Frontiers in Genetics, 2025)
Several missense mutations in the LRRK2 gene are linked to familial Parkinson’s disease (PD). Although LRRK2 mutant mouse models typically lack gross motor impairments, their contribution to non-motor PD symptoms remains largely underexplored. In this study, we showed that the R1441G missense mutation promoted behavioural despair in the forced swim test (FST) and led to anhedonia, reflected in reduced sucrose preference, while the typical expression of helplessness in avoidance learning, induced by undermining locus of control, was unaffected. Notably, these depressive phenotypes emerged predominantly in heterozygous R1441G knock-in (KI) mice, and a similar dominant negative phenotype was evident in the elevated plus maze, with heterozygous mutants exhibiting lower anxiety than wild-type (WT) mice. Together, these results suggest that the R1441G mutation may impact select dimensions of affective function in prodromal adult mice, irrespective of sex. In contrast, no overt behavioural phenotypes were detected in cognitive, social, or motor domains, including associative learning, hippocampus-dependent spatial learning, sensorimotor gating, social interaction, motor coordination, grip strength, or spontaneous locomotor activity. Further investigation is warranted to dissect the mechanisms underlying the domain-specific and seemingly dominant-negative behavioural effects of the R1441G mutation, especially in comparison to the behavioural phenotypes associated with other models of LRRK2 mutations.